Study On Flies Diversity And Effect Of Biotic And Abiotic Factors On Houseflies At Different Farming Systems - Ballakrishnan, Navanithakumar (2024)
A study on the effect of the rearing system and the manure settling floor on the abundance of Musca domestica (fly) was conducted in Kinta district, Perak, Malaysia. The objectives of this study were to determine the diversity of Diptera species in 14 commercial poultry farms with close house and open house systems; the effect of biotic and abiotic factors and wind speed on the abundance of flies in fields with soil and concrete floor types; differences in the housefly index related to relative humidity, the thickness of manure deposited on the floor of the house, the natural manure moisture content, and wet manure were studied on six broiler farms. Knowledge, attitude, and practices (KAP) survey was also carried out to assess the current housefly management and prevention measures in practice. A total of 7,993 flies captured belonged to nine families namely, Muscidae, Calliphoridae, Sacrophagidae, Ulidiidae, Phoridae, Stratiomyidae, Sciaridae, Fannidae and Syrphidae. The Musca domestica was the predominant fly species (p= 0.047) and it represented 74.01% (open house) and 68.26% (closed house) while Megaselia scalaris was the second most abundant species constitutes (21.66% in open house and 30.58% in closed house farming system). In earthen manure settling floor, mean housefly index was 7.67 ± 0.23 heads/30 seconds, p= 0.000 ; bird’s age (12.29 ± 0.48 days, p= 0.057); temperature (29.14 ± 0.07 ℃, p= 0.000); ammonia (0.85 ± 0.04 ppm, p= 0.028); hydrogen sulfide (0.04 ± 0.00 ppm, p= 0.004); wind speed (0.98 ± 0.03 m/s, p= 0.457); relative humidity (56.79 ± 0.27%, p= 0.264); general manure moisture (45.53 ± 1.09%, p= 0.107); wet spot moisture (70.46 ± 1.62%, p= 0.707) and thickness of manure settled (26.13 ± 0.94 mm, p= 0.000).